The hidden Web a sourcebook - Scheeren, William O. (Libraries Unlimited, 2012)
Google is certainly a useful Internet search tool for general topics, but most of the information available on the Invisible Web can't be found through Google. This book explains the value of the Invisible Web and how to access it.